2021
DOI: 10.1016/j.celrep.2021.108993
|View full text |Cite
|
Sign up to set email alerts
|

CD169+ lymph node macrophages have protective functions in mouse breast cancer metastasis

Abstract: Highlights d Lymph node CD169 + macrophages massively proliferate and expand in murine breast cancer d Medullary and subcapsular sinus macrophages strongly respond to tumor stimuli d Depletion of subcapsular sinus macrophages strongly favors lung metastases d The anti-metastatic effect of CD169 + LN macrophages depends on B cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 65 publications
5
33
0
Order By: Relevance
“…They also found that the capture of tumor-derived exosomes by SMs inhibited the proliferation of pro-tumor B cells in the lymph nodes; an immunohistochemical analysis using human samples revealed the presence of melanoma-derived antigens in melanoma-free draining lymph nodes. Similar effects of SMs on B-cell proliferation in murine 4T1 and MMTV-PyMT mammary carcinoma models were reported by Tacconi et al [28]. These authors demonstrated lung metastasis of cancer cells in SM-depleted mice, but depletion of B cells using an anti-CD20 antibody significantly suppressed lung metastasis.…”
Section: The Function Of Sms In Protumor Function Of B-lymphocytes In Micesupporting
confidence: 79%
“…They also found that the capture of tumor-derived exosomes by SMs inhibited the proliferation of pro-tumor B cells in the lymph nodes; an immunohistochemical analysis using human samples revealed the presence of melanoma-derived antigens in melanoma-free draining lymph nodes. Similar effects of SMs on B-cell proliferation in murine 4T1 and MMTV-PyMT mammary carcinoma models were reported by Tacconi et al [28]. These authors demonstrated lung metastasis of cancer cells in SM-depleted mice, but depletion of B cells using an anti-CD20 antibody significantly suppressed lung metastasis.…”
Section: The Function Of Sms In Protumor Function Of B-lymphocytes In Micesupporting
confidence: 79%
“…We demonstrated that SSMs possess anti-tumor activity by showing that in their absence tumors grow faster (8). These observations have been confirmed in additional tumor types (9,10). The analyses above start to narrow down which potential biological processes may be at the root of SSM biology in cancer.…”
Section: Resultssupporting
confidence: 62%
“…We have recently demonstrated that SSMs possess anti-tumor activity because in their absence tumors grow faster ( 8 ). These observations have been confirmed in additional tumor types ( 9 , 10 ). However, the cellular and molecular mechanisms responsible for SSM anti-tumor activity are still unknown.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In addition, they play a critical role in the initiation of the immune responses against immune complexes and virus [16][17][18] as well as promoting humoral immunity 19,20 . Despite the role of macrophages against infectious pathogens has been largely demonstrated, their involvement in the response against tumor remains somehow controversial [21][22][23][24][25][26][27] . This is mainly due to the ability of these cells to activate either anti-or pro-tumoral responses, according to their cell plasticity, that allows them being dicotomically classified in M1 and M2 macrophages 28,29 .…”
Section: Introductionmentioning
confidence: 99%